Colposcopic and microbiological correlation in patients with vaginal infections: a prospective study - Sharma, Reena; Mohi, Manjit Kaur; Kaur, Khush Preet; Walia, Geeta (International Journal of Research in Medical Sciences, 2021)
Background: Objective of the study was to evaluate the association of abnormal vaginal flora with pathological colposcopic and microbiological findings. Methods: The present study was conducted in outpatient’s department of Obstetrics and Gynaecology, Government Medical College, Patiala. We studied 300 cases with symptoms and signs of vaginal infections in reproductive age group (15-49 years). After taking detailed history and examination, samples of vaginal discharge were collected for microbiological analysis and patients were subjected to colposcopy. Recorded data was analysed to find out any association of abnormal vaginal flora with pathological colposcopic and microbiological analysis. Results: The prevalence rate of vaginal infections was 31% among patients who reported to us with symptoms and signs of vaginal infections. The most common micro-organism detected was B. vaginosis (BV) in 14%, C. albicans (C) in 12% and T. vaginalis (T) in 3.33%. The normal colposcopic findings were observed in 81.33% and abnormal colposcopic findings were noted in 18.67% of the patients which were vaginal hyperaemia in 9%, chronic cervicitis in 5.33%, small iodine negative area in 2.33%, keratosis in 1.33% and cervical polyp in 0.67% of the patients. Conclusions: We concluded that vaginal discharge is a common gynaecological complaint and vaginal infections are an important cause of the vaginal discharge thus leading to significant proportion of female morbidity in reproductive age group. So, vaginitis and vaginal discharge highlights the importance of microbiological investigations to find out the causative organisms and the specific findings due to particular micro-organism can be correlated colposcopically and specific treatment can be provided.